$
\begin{array}{*{20}c}
\begin{array}{l}
a. \\
\\
\\
\\
\\
\\
\end{array} & \begin{array}{l}
3x^2 = 5x \\
3x^2 - 5x = 0 \\
x(3x - 5) = 0 \\
x = 0 \vee 3x - 5 = 0 \\
x = 0 \vee 3x = 5 \\
x = 0 \vee x = 1\frac{2}{3} \\
\end{array} \\
\end{array}
$ |
$
\begin{array}{*{20}c}
\begin{array}{l}
b. \\
\\
\\
\\
\end{array} & \begin{array}{l}
(3x + 3)(2x - 5) = 0 \\
3x + 3 = 0 \vee 2x - 5 = 0 \\
3x = - 3 \vee 2x = 5 \\
x = - 1 \vee x = 2\frac{1}{2} \\
\end{array} \\
\end{array}
$ |
$
\begin{array}{*{20}c}
\begin{array}{l}
c. \\
\\
\\
\\
\end{array} & \begin{array}{l}
(3x - 1)^2 = 16 \\
3x - 1 = - 4 \vee 3x - 1 = 4 \\
3x = - 3 \vee 3x = 5 \\
x = - 1 \vee x = 1\frac{2}{3} \\
\end{array} \\
\end{array}
$ |
$
\begin{array}{*{20}c}
\begin{array}{l}
d. \\
\\
\\
\\
\\
\\
\\
\end{array} & \begin{array}{l}
(x + 2)^2 + (x + 3)^2 = 1 \\
x^2 + 4x + 4 + x^2 + 6x + 9 = 1 \\
2x^2 + 10x + 13 = 1 \\
2x^2 + 10x + 12 = 0 \\
x^2 + 5x + 6 = 0 \\
(x + 2)(x + 3) = 0 \\
x = - 2 \vee x = - 3 \\
\end{array} \\
\end{array}
$ |
$
\begin{array}{*{20}c}
\begin{array}{l}
e. \\
\\
\\
\\
\\
\\
\\
\\
\\
\\
\\
\\
\\
\\
\end{array} & \begin{array}{l}
8x^2 + 2x - 3 = 0 \\
8\left( {x^2 + \frac{1}{4}x} \right) - 3 = 0 \\
8\left( {\left( {x + \frac{1}{8}} \right)^2 - \frac{1}{{64}}} \right) - 3 = 0 \\
8\left( {x + \frac{1}{8}} \right)^2 - \frac{1}{8} - 3 = 0 \\
8\left( {x + \frac{1}{8}} \right)^2 - 3\frac{1}{8} = 0 \\
8\left( {x + \frac{1}{8}} \right)^2 = 3\frac{1}{8} \\
\left( {x + \frac{1}{8}} \right)^2 = \frac{{25}}{{64}} \\
x + \frac{1}{8} = - \frac{5}{8} \vee x + \frac{1}{8} = \frac{5}{8} \\
x = - \frac{3}{4} \vee x = \frac{1}{2} \\
\end{array} \\
\end{array}
$ |
$
\begin{array}{*{20}c}
\begin{array}{l}
f. \\
\\
\\
\end{array} & \begin{array}{l}
12x^2 = 144 \\
x^2 = 12 \\
x = - \sqrt {12} \vee x = \sqrt {12} \\
\end{array} \\
\end{array}
$ |